MANAJEMEN LALU LINTAS SATU ARAH KAWASAN BARAT SEMARANG - Harfit Langlang Buono Putra; Yogreza Berlyawardhana; Epf. Eko Yulipriyono; Amelia Kusuma Indriastuti (Jurnal Karya Teknik Sipil, 2013)
Western Region of Semarang beside as center of business, it also as the center of public services so at the peak period the volume of vehicle in some road getting increase. The increase of vehicle’s volume will cause traffic jam. Roads with the traffic jam potential is Sugiyopranoto, Imam Bonjol, and Pemuda. Then the idea of one way traffic management proposed with the purpose to determine the traffic performance at existing condition and provide a recommendation about the better traffic regulation. Observation such as traffic survey has been done on roads and intersections in road network in the west region of Semarang. Analysis of traffic performance based on Indonesia’s Highway Capacity Manual (IHCM) 1997 with an analysis of existing saturated conditions at peak hours in the morning, afternoon, and evening as a benchmark for short-term design. One way traffic management that applied are the change of green time at the signalized intersection, the route, traffic diversion by the application of the one way traffic chain on the road network, traffic facilities, and geometric. The analysis result of roads and intersection in the region shows the performance with degree of saturation >0,75. The ideal limit is ≤ 0,75. The result of the intersection analysis also showed unsatisfactory performance. The degree of saturation is high and delay time of intersection still large.so the one way traffic management applied on the Sugiyopranoto road, the entire segment of Imam Bonjol Road, The entire segment of Pemuda road, and Pierre Tendean road. The intersection changes is by removing the signal of Poncol intersection and Tendean intersection. Several signal at Tugumuda intersection suchas signal from Sugiyopranoto, signal from Pemuda, and the signal in front of Sutomo also removed. The results of the analysis for one-way condition showed better performance. The traffic flow is also distributed optimally. The based parameter is the change of speed and pace time that can be felt directly by road users. The design for the implementation of one-way traffic system can be said good for the treatment of short-term problems. The conclusion that can be drawn is the performance of roads and intersections in the West Region Semarang get better when applied to one-way traffic management.